Silicon-carbon composite material and preparation method thereof, negative pole piece, battery and electric device

By gasifying the silicon powder under vacuum and mixing the porous carbon material with a gaseous silicon source, a silicon-carbon composite material with nanosilicon particles distributed inside the porous carbon material was prepared, which solved the problem of uneven stress caused by volume changes in the silicon-based negative electrode material, and achieved the effect of improving the circulation performance and the first Coulomb efficiency.

CN119905536APending Publication Date: 2025-04-29WANHUA CHEM GRP BATTERY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311415439.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The silicon-based negative electrode material has uneven stress distribution due to huge volume changes in the de-lithium de-embedding process, which is prone to powdering and cracking, resulting in poor circulation performance.

Method used

The silicon-carbon composite material with nano-silicon particles is prepared by combining porous carbon materials and gasifying the silicon powder under vacuum conditions and mixing the porous carbon material with gaseous silicon source.

Benefits of technology

The risk of volume expansion, cracking and powderization of silicon-carbon composite materials during charging and discharging is reduced, cycling performance is improved, and high first-time Coulomb efficiency is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905536A_ABST
    Figure CN119905536A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material and a preparation method thereof, a negative pole piece, a battery and an electric device. The silicon-carbon composite material comprises a porous carbon material and nanometer silicon particles, at least a part of the nanometer silicon particles are distributed in the porous carbon material, and the average particle size of the nanometer silicon particles is 2-10 nm; on the basis of the mass of the silicon-carbon composite material, the content of oxygen in the silicon-carbon composite material is less than or equal to 0.5 wt%. Therefore, on one hand, the risks of volume expansion, cracking and pulverization of the silicon-carbon composite material in the charging and discharging process can be reduced, the cycle performance can be improved, and on the other hand, relatively high initial coulombic efficiency can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically relates to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device. Background Art

[0002] Silicon-based negative electrode materials have become the next generation of negative electrode materials with great potential due to their extremely high theoretical capacity of 4200mAh / g. However, compared with traditional negative electrode materials such as graphite, silicon-based negative electrode materials also have many defects, the most fatal of which is the uneven stress distribution of Si particles due to the huge volume change during the lithium removal / insertion process, which is very easy to pulverize, crack, and even separate from the current collector, resulting in poor cycle performance. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present invention is to provide a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, a battery and an electric device to reduce the volume expansion, cracking and pulverization risks of silicon-containing negative electrode active materials during charging and discharging, and improve the cycle performance and the first coulomb efficiency.

[0004] The first aspect of the present invention provides a silicon-carbon composite material, comprising: a porous carbon material and nano-silicon particles, at least a portion of the nano-silicon particles are distributed inside the porous carbon material, wherein:

[0005] The particle size of the nano silicon particles is 2nm to 10nm;

[0006] Based on the mass of the silicon-carbon composite material, the oxygen content in the silicon-carbon composite material is ≤0.5wt%.

[0007] The silicon-carbon composite material of the present invention has the following beneficial effects: on the one hand, it can reduce the risk of volume expansion, cracking and pulverization of the silicon-carbon composite material during the charge and discharge process, thereby improving the cycle performance; on the other hand, it can also obtain a higher first coulombic efficiency.

[0008] In addition, the silicon-carbon composite material according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, the mass ratio of the nano-silicon particles to the porous carbon material is 0.90 to 1.25, thereby enabling the silicon-carbon composite material to obtain a higher specific capacity while also taking into account the volume expansion of the silicon-carbon composite material.

[0010] In some embodiments of the present invention, the silicon-carbon composite material meets at least one of the following three conditions: the volume particle size Dv50 is 3 μm to 10 μm, the specific surface area is ≤10 m 2 / g, true density is 1.8g / cm3 ~2.0g / cm 3 Meeting the given conditions is beneficial to improving the cycle performance of the battery.

[0011] In some embodiments of the present invention, the specific surface area of ​​the porous carbon material is ≥1500m 2 This is beneficial to the sufficient deposition and uniform distribution of nano-silicon particles, thereby obtaining a silicon-carbon composite material with a lower specific surface area, and is also beneficial to improving the volume expansion effect of nano-silicon particles.

[0012] In some embodiments of the present invention, the porous carbon material includes at least one of activated carbon, natural graphite, artificial graphite, and carbon nanotubes.

[0013] In some embodiments of the present invention, at least a portion of the outer surface of the silicon-carbon composite material is further provided with a carbon coating layer, thereby improving the conductivity and stability of the silicon-carbon composite material.

[0014] In some embodiments of the present invention, the thickness of the carbon coating layer is 1nm to 100nm; and / or the mass percentage of the carbon coating layer in the silicon-carbon composite material is 1wt% to 6wt%. This is conducive to further taking into account the volume energy density of the negative electrode sheet and the battery.

[0015] A second aspect of the present invention provides a method for preparing the above silicon-carbon composite material, comprising:

[0016] Gasifying silicon powder under vacuum conditions to obtain a gaseous silicon source;

[0017] The porous carbon material is mixed with the gaseous silicon source in a fluidized state so that the gaseous silicon source is deposited on the surface of the porous carbon, thereby obtaining a silicon-carbon composite material including the porous carbon material and nano-silicon particles, wherein at least a portion of the nano-silicon particles are distributed inside the porous carbon material.

[0018] The method for preparing a silicon-carbon composite material according to the above embodiment of the present invention has the following beneficial effects: it is not only simple to operate, highly safe, and low in cost, but is also more conducive to the uniform deposition of nano-silicon particles on the surface and inside of the porous carbon material, and can obtain nano-silicon particles with a particle size of 2nm to 10nm and control the oxygen content in the silicon-carbon composite material to below 0.5wt%, so that the prepared silicon-carbon composite material has both good cycle stability and improved first coulombic efficiency.

[0019] In some embodiments of the present invention, the volume particle size Dv50 of the silicon powder is 200 nm to 600 nm, which is not only conducive to improving the gasification efficiency, but also reduces the difficulty and cost of preparation.

[0020] In some embodiments of the present invention, the silicon powder includes metallic silicon and / or polycrystalline silicon, which is helpful to reduce the impurity content of the finally obtained silicon-carbon composite material.

[0021] In some embodiments of the present invention, the vacuum degree of the vacuum condition is 5 Pa to 50 Pa. This can strictly control the oxygen content in the gaseous silicon source on the one hand, and promote the gasification of silicon powder and the escape of the gaseous silicon source on the other hand.

[0022] In some embodiments of the present invention, the temperature of the gasification treatment is 1200° C. to 1800° C. and the time is 2 hours to 12 hours, thereby achieving the gasification of silicon powder and taking into account the gasification efficiency.

[0023] In some embodiments of the present invention, the volume particle size Dv50 of the porous carbon material is 3 μm to 6 μm, which is beneficial for fully mixing the porous carbon material and the gaseous silicon source, and also for regulating the particle size of the final silicon-carbon composite material to be within the expected range.

[0024] In some embodiments of the present invention, the temperature of the mixing treatment is 400° C. to 600° C. This is beneficial to increase the number of nano-silicon nuclei and uniform deposition in the porous carbon material, and increase the deposition amount of the gaseous silicon source in the porous carbon material.

[0025] In some embodiments of the present invention, the mixing process is performed under vacuum conditions or a protective atmosphere, thereby further strictly controlling the oxygen content in the finally obtained silicon-carbon composite material.

[0026] In some embodiments of the present invention, the device for implementing the method includes a gasification zone and a collection zone, the gasification zone and the collection zone can be connected to each other, the gasification treatment is carried out in the gasification zone, the mixing treatment is carried out in the collection zone, and the collection zone is rotatable relative to the gasification zone.

[0027] In some embodiments of the present invention, the method for preparing a silicon-carbon composite material further comprises: depositing a carbon coating layer on the surface of the silicon-carbon composite material using a carbon source gas under a protective atmosphere.

[0028] In some embodiments of the present invention, a carbon source gas and a protective gas are introduced into the silicon-carbon composite material in a fluidized state to deposit a carbon coating layer on the surface of the silicon-carbon composite material, thereby further facilitating the uniform deposition of carbon on the surface of the silicon-carbon composite material.

[0029] In some embodiments of the present invention, the volume filling rate of the porous carbon material in the collection area is 1% to 10%, which is beneficial for both making the porous carbon material have a better fluidized state and taking into account the reaction efficiency.

[0030] In some embodiments of the present invention, at least one of the following conditions is met: the temperature of depositing the carbon coating layer is 500°C to 700°C, and the time is 2h to 10h; the volume ratio of the carbon source gas to the protective gas is (5L to 10L): (1L to 3L); the carbon source gas includes at least one of methanol, acetone, methane, ethane, propane, and acetylene; the protective gas includes argon and / or nitrogen.

[0031] The third aspect of the present invention provides a negative electrode plate, which comprises: the silicon-carbon composite material mentioned above; and / or the silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material mentioned above. The negative electrode plate has good volume stability during use, which is conducive to making the battery have good cycle performance, high energy density and improved first coulomb efficiency.

[0032] The fourth aspect of the present invention provides a battery, which includes: the above-mentioned negative electrode plate. The battery can have good cycle performance, high energy density and improved first coulomb efficiency.

[0033] The fifth aspect of the present invention provides an electric device, which includes the above-mentioned battery. The battery life of the electric device and the service life of the battery are relatively long.

[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of a method for preparing a silicon-carbon composite material according to an embodiment of the present invention.

[0036] Figure 2 The present invention is a flow chart of a method for preparing a silicon-carbon composite material according to another embodiment of the present invention.

[0037] Figure 3 1 is a structural diagram of an apparatus for preparing a silicon-carbon composite material according to an embodiment of the present invention.

[0038] Figure 4 4 is a structural diagram of an apparatus for preparing a silicon-carbon composite material according to another embodiment of the present invention.

[0039] Figure 5 It is a scanning electron microscope image of the cross section of the silicon-carbon composite material samples prepared in Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0040] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0041] On a microscopic scale, when lithium is inserted into silicon-based negative electrode active materials, lithium ions are first enriched on the particle surface, while the lithium ion concentration at the center of the particle is very low. Therefore, there is a concentration gradient of lithium ions in the radial direction of the particle, and the lithium insertion rate of Si near the surface is greater than that of Si near the center. Because Si undergoes a huge volume expansion when lithium is inserted, the expansion rate of Si near the surface does not match the expansion rate of Si near the center, which can easily lead to uneven stress inside and outside the particles, and then cracking and pulverization, which not only affects the contact between the silicon-based negative electrode active material and the current collector, making the silicon-based negative electrode active material easily separated from the current collector, causing rapid attenuation of the battery capacity, but also the huge volume change of the silicon-based negative electrode active material during the charge and discharge process, and it is easy to form an unstable SEI film. During the charge and discharge process, the volume change of Si can easily lead to the rupture and regeneration of the SEI film, resulting in continuous consumption of electrolyte and the formation of thick and uneven SEI film, affecting the specific capacity and ion diffusion of the battery.

[0042] In view of this, the first aspect of the present invention provides a silicon-carbon composite material. According to an embodiment of the present invention, the silicon-carbon composite material comprises: a porous carbon material and nano-silicon particles, at least a portion of the nano-silicon particles are distributed inside the porous carbon material, wherein: the particle size of the nano-silicon particles is 2nm to 10nm; based on the mass of the silicon-carbon composite material, the oxygen content in the silicon-carbon composite material is ≤0.5wt%.

[0043] According to the silicon-carbon composite material of the above embodiment of the present invention, the smaller the size of Si particles, the smaller the degree of uneven stress inside and outside the particles of the silicon-carbon composite material during the charge and discharge process, and the smaller the probability of pulverization and cracking. For example, when the particle size of Si particles is less than 80nm, cracking and pulverization basically do not occur. Taking lithium-ion batteries as an example, in the present invention, the particle size of silicon particles in the silicon-carbon composite material is controlled within the given range, which can significantly improve the problem of mismatch between the expansion rate of Si near its surface position and the expansion rate of Si near its center position when the silicon-carbon composite material particles are embedded with lithium, reduce the stress difference inside and outside the particles, reduce the volume expansion and cracking and pulverization risks of the silicon-carbon composite material particles during the charge and discharge process, and thus improve the volume stability and cycle performance of the silicon-carbon composite material. Furthermore, porous carbon materials are used as carriers of nano-silicon particles. On the one hand, the volume change of carbon materials during the charge and discharge process is small, and they have good cycle stability and conductivity. On the other hand, their porous structure can be used to further alleviate the volume expansion effect of Si during the charge and discharge process, and thus further improve the volume stability and cycle performance of the silicon-carbon composite material. In addition, compared with Si, the volume expansion of SiOx during the lithium insertion process is relatively reduced, which is beneficial to further improve the cycle performance of the silicon-carbon composite material, but it will reduce the first coulomb efficiency. At the same time, the particle size of the nano-silicon particles and the oxygen content in the silicon-carbon composite material are controlled within the given range, which can not only improve the volume stability and capacity retention rate of the silicon-carbon composite material during the charge and discharge process, but also take into account the higher first effect, which is conducive to obtaining better cycle performance, higher specific capacity and first coulomb efficiency. Therefore, the silicon-carbon composite material of the present invention has the following beneficial effects: on the one hand, it can reduce the risk of volume expansion, cracking and pulverization of the silicon-carbon composite material during the charge and discharge process, improve the cycle performance, and on the other hand, it can also obtain a higher first coulomb efficiency.

[0044] According to an embodiment of the present invention, the particle size of the nano silicon particles is 2nm-10nm, for example, 2nm, 5nm, 8nm, 10nm, etc. In the present invention, the particle size of the nano silicon particles can be characterized by HRTEM electron microscopy (ie, high resolution transmission electron microscopy).

[0045] According to an embodiment of the present invention, the oxygen content in the silicon-carbon composite material is ≤0.5wt%, for example, it can be 0.5wt%, 0.4wt%, ≤0.3wt%, ≤0.2wt%, ≤0.1wt%, etc. In the present invention, the oxygen content in the silicon-carbon composite material can be tested by an inert gas fusion infrared method or the like, and specific reference can be made to GB / T 38976-2020.

[0046] In some embodiments of the present invention, the mass ratio of porous carbon material to nano silicon particles can be 0.90 to 1.25, for example, 0.90, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, etc. In the present invention, the content of porous carbon material in the silicon-carbon composite material can be tested by a sulfur-carbon analyzer and the like, and the composition and content of other elements can be obtained by combining ICP elemental analysis and the like, and the content of nano silicon particles can be obtained by subtraction. In the present invention, controlling the mass ratio of porous carbon material to nano silicon particles within this range can not only enable the silicon-carbon composite material to obtain a higher specific capacity, but also take into account the volume expansion of the silicon-carbon composite material, and control its volume expansion during the charge and discharge process within a reasonable range, and then using the silicon-carbon composite material in the negative electrode sheet can improve the cycle performance of the battery, which is conducive to obtaining better cycle stability and longer cycle life.

[0047] In some embodiments of the present invention, the silicon-carbon composite material satisfies at least one of the following three conditions: the volume particle size Dv50 can be 3 μm to 10 μm, for example, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, etc.; the specific surface area can be ≤10m 2 / g, for example, 10m 2 / g, ≤8m 2 / g, ≤5m 2 / g, ≤3m 2 / g, etc.; the true density can be 1.8g / cm 3 ~2.0g / cm 3 , for example, it can be 1.8 g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3Etc. In the present invention, the volume particle size Dv50 of the silicon-carbon composite material refers to the particle size corresponding to the cumulative volume distribution percentage reaching 50%, which can be measured by a laser diffraction particle size analyzer with reference to the standard GB / T 19077-2016. Controlling the volume particle size Dv50 of the silicon-carbon composite material within the above range is beneficial to obtaining a higher compaction density and improving the volume energy density of the battery on the one hand; on the other hand, it is also beneficial to obtain a suitable specific surface area, more ion diffusion channels and shorter ion diffusion paths, and improve the electrochemical performance of the battery. In the present invention, the test method for the specific surface area of ​​the silicon-carbon composite material includes a nitrogen adsorption and desorption test. Controlling the specific surface area of ​​the silicon-carbon composite material within the above range is beneficial to obtaining more ion diffusion channels and shorter ion diffusion paths, improving the electrochemical performance of the battery, and at the same time, it can also reduce the contact area between the silicon-carbon composite material and the electrolyte to a certain extent, reduce the capacity loss caused by the formation of the SEI film during the first cycle, and improve the first coulomb efficiency. In the present invention, the true density of the silicon-carbon composite material can be calculated by testing the mass and effective volume of the silicon-carbon composite material in general. The effective volume is the volume of the silicon-carbon composite material minus the volume of the open pores and the closed pores. The silicon-carbon composite material can be placed in a measuring container, a liquid medium is added, and the liquid is allowed to fully infiltrate the open pores of the particles. The effective volume is obtained by subtracting the volume of the liquid medium from the measured volume. In the present invention, controlling the true density of the silicon-carbon composite material within the above range is, on the one hand, conducive to enabling the battery to obtain a higher volume energy density, and on the other hand, making the volume particle size Dv50 and / or specific surface area of ​​the silicon-carbon composite material and the true density meet the above range at the same time, and is also conducive to further taking into account the volume expansion effect of the silicon-carbon composite material during the charge and discharge process, and improving the cycle performance of the battery during the cycle process.

[0048] In some embodiments of the present invention, the specific surface area of ​​the porous carbon material is ≥ 1500 m 2 / g, for example, 1500m 2 / g, ≥1600m 2 / g, ≥1700m 2 / g, ≥1800m 2 / g, ≥2000m 2 / g, etc. The specific surface area of ​​the porous carbon material meets the above range. On the one hand, it can provide a larger attachment area for the nano-silicon particles, which is conducive to the full deposition and uniform distribution of the nano-silicon particles, and obtain a silicon-carbon composite material with a lower specific surface area. On the other hand, it is also conducive to providing a larger accommodating space for the volume expansion of the nano-silicon particles, thereby improving the volume expansion effect of the nano-silicon particles.

[0049] In some embodiments of the present invention, the porous carbon material may include, but is not limited to, at least one of activated carbon, natural graphite, artificial graphite, and carbon nanotubes.

[0050] In some embodiments of the present invention, at least a portion of the outer surface of the silicon-carbon composite material may be provided with a carbon coating layer. Providing the carbon coating layer can not only prevent the silicon-carbon composite material from directly contacting the electrolyte and inhibit the excessive growth of the SEI film, but also help to improve the conductivity of the silicon-carbon composite material, and also help to further limit and buffer the volume expansion of the silicon-carbon composite material, and improve the cycle stability of the silicon-carbon composite material during the charge and discharge process.

[0051] In some embodiments of the present invention, the thickness of the carbon coating layer may be 1 nm to 100 nm, for example, 1 nm, 5 nm, 10 nm, 20 nm, 50 nm, 80 nm or 100 nm, etc.; and / or, the mass percentage of the carbon coating layer in the silicon-carbon composite material may be 1 wt% to 6 wt%, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, etc. Meeting the given conditions is conducive to further taking into account the volume energy density of the negative electrode sheet and the battery.

[0052] At present, the method of nano-sizing Si particles in the relevant field generally adopts mechanical wet grinding, which uses the strong shear force between the grinding media to break the Si particles to the nanometer level. However, this method is difficult to avoid the contact between air or water and nano-Si particles, and the oxygen content of the final product is high, resulting in a low initial efficiency of the product. In addition, the limit particle size of Si particles prepared by the grinding method is about 80nm, and it is difficult to prepare Si particles with a smaller particle size. Reducing the Si particles is conducive to increasing its deposition amount in the carbon material. In recent years, a method of using chemical vapor deposition to prepare nano-Si / C composite materials has been proposed, such as preparing nano-Si / C composite materials by controlling the decomposition of silane on the surface of carbon materials, but this method is costly, and the operation is difficult when using silane, and the requirements for industrial production are high.

[0053] In view of this, the second aspect of the present invention provides a method for preparing the above silicon-carbon composite material. According to an embodiment of the present invention, referring to Figure 1 It is understood that the method includes: gasifying silicon powder under vacuum conditions to obtain a gaseous silicon source; mixing a porous carbon material with the gaseous silicon source under a fluidized state so that the gaseous silicon source is deposited on the surface of the porous carbon to obtain a silicon-carbon composite material including a porous carbon material and nano-silicon particles, with at least a portion of the nano-silicon particles distributed inside the porous carbon material.

[0054] According to the method for preparing silicon-carbon composite materials according to the above embodiment of the present invention, a nano-silicon-carbon composite material is prepared by adopting a bottom-up physical vapor deposition method, which can not only make silicon uniformly deposited on the surface and inside of the porous carbon material, but also obtain nano-silicon particles with a particle size of 2nm to 10nm, and at the same time improve the bonding strength of Si-C; further, the silicon powder is gasified under vacuum conditions, and the oxygen content in the final silicon-carbon composite material can be controlled below 0.5wt%; in addition, the porous carbon material is mixed with a gaseous silicon source under a fluidized state, which is further conducive to the uniform deposition of silicon on the surface and inside of the porous carbon material, and preferably, the mixing process can also be carried out under vacuum conditions; furthermore, the method is also conducive to obtaining amorphous silicon materials under positive pressure, slightly positive pressure or negative pressure by adjusting the system pressure and temperature of the silicon deposition reaction. Therefore, compared with the chemical vapor deposition method, the method for preparing the silicon-carbon composite material of the above embodiment of the present invention is not only simple to operate, highly safe, and low in cost, but also more conducive to the uniform deposition of nano-silicon particles on the surface and inside of the porous carbon material, and can obtain nano-silicon particles with a particle size of 2nm to 10nm and control the oxygen content in the silicon-carbon composite material to below 0.5wt%, so that the prepared silicon-carbon composite material has both good cycle stability and improved first coulombic efficiency.

[0055] Reference below Figures 1 to 4 The method for preparing the silicon-carbon composite material is described in detail.

[0056] S1: Gasify silicon powder under vacuum conditions to obtain gaseous silicon source

[0057] In some embodiments of the present invention, the volume particle size Dv50 of the silicon powder may be 200nm to 600nm, such as 200nm, 300nm, 400nm, 500nm, 600nm, etc. The volume particle size Dv50 of the silicon powder may also be measured by a laser diffraction particle size analyzer with reference to the standard GB / T19077-2016. Selecting silicon powder in the above volume particle size range is not only conducive to improving gasification efficiency, but also reduces preparation difficulty and cost.

[0058] In some embodiments of the present invention, silicon powder may include metallic silicon and / or polycrystalline silicon. In the present invention, metallic silicon refers to industrially purified elemental silicon, and the silicon content is preferably not less than 99%, such as not less than 99.2%, 99.5%, etc.; the purity of polycrystalline silicon is higher than that of metallic silicon, and is usually purified from metallic silicon. Selecting the above silicon powder can further reduce the impurity content of the final silicon-carbon composite material, thereby reducing the negative impact that impurities may have on the electrochemical properties of the silicon-carbon composite material.

[0059] In some embodiments of the present invention, the vacuum degree of the vacuum condition can be 5Pa to 50Pa, such as 5Pa, 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, etc. When the silicon powder is gasified under vacuum conditions, the vacuum degree is controlled within the above range. On the one hand, the oxygen content in the gaseous silicon source can be strictly controlled, and the oxygen content in the final silicon-carbon composite material can be controlled below 0.5wt%, and the operability is good. On the other hand, it is also conducive to promoting the gasification of silicon powder and the escape of the gaseous silicon source, making the gaseous silicon source more conducive to the migration of the gaseous silicon source toward the porous carbon material, and promoting the deposition of the gaseous silicon source in the porous carbon material.

[0060] In some embodiments of the present invention, the temperature of the gasification treatment may be 1200°C to 1800°C, and the time may be 2h to 12h. For example, the temperature of the gasification treatment may be 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1400°C to 1800°C, etc.; the time of the gasification treatment may be 2h, 4h, 6h, 8h, 10h, 12h, etc. Gasification treatment of silicon powder under the above conditions can not only realize the gasification of silicon powder, but also take into account the gasification efficiency.

[0061] S2: Mixing the porous carbon material with a gaseous silicon source in a fluidized state, and depositing the gaseous silicon source on the surface of the porous carbon to obtain a silicon-carbon composite material including the porous carbon material and nano-silicon particles, wherein at least a portion of the nano-silicon particles are distributed inside the porous carbon material.

[0062] According to an embodiment of the present invention, the porous carbon material is mixed with the gaseous silicon source in a fluidized state, which is further conducive to the uniform deposition of silicon on the surface and inside of the porous carbon material. Exemplarily, the system pressure of the process can be adjusted to be lower than the system pressure during the gasification of silicon powder, so as to promote the migration of the gaseous silicon source to the region of the porous carbon material. In addition, it should be noted that the method of placing the porous carbon material in a fluidized state is not particularly limited, and those skilled in the art can flexibly select according to actual needs, for example, physical conditions such as rotation or stirring can be used to place the porous carbon material in a fluidized state.

[0063] In some embodiments of the present invention, the volume particle size Dv50 of the porous carbon material can be 3μm to 6μm, for example, 3μm, 4μm, 5μm, 6μm, etc. The volume particle size Dv50 of the porous carbon material can also be measured by a laser diffraction particle size analyzer with reference to the standard GB / T 19077-2016. Controlling the particle size of the porous carbon material to meet the above range is beneficial to the full mixing of the porous carbon material and the gaseous silicon source, promoting the uniform deposition of silicon on the surface and inside of the porous carbon material, and is also beneficial to regulating the particle size of the final silicon-carbon composite material to obtain a silicon-carbon composite material with a volume particle size Dv50 of 3μm to 10μm. Furthermore, the specific surface area of ​​the porous carbon material can be ≥1500m 2 / g, the corresponding beneficial effects have been explained in the previous part and will not be repeated here.

[0064] It should be noted that the optional range of porous carbon materials has been described in the previous section and will not be repeated here. In addition, during the mixing process, the mass ratio of the gaseous silicon source to the porous carbon material can be controlled, such as making the gaseous silicon source excessive relative to the porous carbon material, specifically, the mass ratio of the gaseous silicon source to the porous carbon material can be 1 to 1.5, etc., so that the mass ratio of the porous carbon material and the nano-silicon particles of the final composite material is 0.90 to 1.25.

[0065] In some embodiments of the present invention, the temperature of the mixing treatment may be 400° C. to 600° C., for example, 400° C., 450° C., 500° C., 550° C., 600° C., etc. Controlling the temperature of the mixing treatment within the above range is beneficial to promoting the migration of the gaseous silicon source and controlling the nucleation rate of the nano-silicon particles, which is beneficial to increasing the number of nano-silicon nuclei and uniform deposition in the porous carbon material, and increasing the deposition amount of the gaseous silicon source in the porous carbon material.

[0066] In some embodiments of the present invention, the mixing process can be carried out under vacuum conditions or protective atmosphere, wherein the protective atmosphere can be a non-oxygen atmosphere, such as a nitrogen atmosphere, an inert gas protective atmosphere, or a mixed atmosphere of nitrogen and inert gas. Under the above-mentioned atmospheric conditions, the porous carbon material is mixed with the gaseous silicon source in a fluidized state, and the oxygen content in the silicon-carbon composite material can be further strictly controlled, and the oxygen content in the finally obtained silicon-carbon composite material can be controlled to be below 0.5wt%.

[0067] In some embodiments of the present invention, reference Figure 3It is understood that the device for preparing a silicon-carbon composite material may include a gasification zone and a collection zone, the gasification zone and the collection zone may be connected, the gasification treatment (ie, step S10) may be performed in the gasification zone, the mixing treatment (ie, step S20) may be performed in the collection zone, and the collection zone may be rotatable relative to the gasification zone. The rotatable arrangement of the collection zone relative to the gasification zone is conducive to the fluidization of the porous carbon material. Among them, the gasification zone and the collection zone may be independently provided with heating elements. Exemplarily, in the actual preparation process, silicon powder may be placed in the gasification zone, the porous carbon material may be placed in the collection zone, the device may be evacuated to a vacuum degree of 5Pa to 50Pa, the collection zone may be rotated to fluidize the porous carbon material, the gasification zone and the collection zone may be heated respectively, the temperature of the gasification zone may be 1200°C to 1800°C, the temperature of the collection zone may be 400°C to 600°C, the silicon powder may be vaporized at high temperature and migrate to the collection zone, and may be fully mixed with the porous carbon material in a fluidized state, so as to achieve nano-deposition on the surface and inside of the porous carbon material. Furthermore, a valve (not shown) can be set between the gasification zone and the collection zone, and the valve is used to realize the opening and closing state between the gasification zone and the collection zone. The adoption of this setting is beneficial to pre-gasify the silicon powder in the gasification zone at the initial stage of the reaction, and then supply the gaseous silicon source to the collection zone after obtaining the gaseous silicon source.

[0068] In some embodiments of the present invention, the volume filling rate of the porous carbon material in the collection area may be 1% to 10%, for example, 1%, 3%, 5%, 7%, 10%, etc. Meeting the above conditions is beneficial for both making the porous carbon material have a better fluidized state and taking into account the reaction efficiency.

[0069] Furthermore, the method for preparing the silicon-carbon composite material may further include step S3.

[0070] S3: Depositing a carbon coating layer on the surface of the silicon-carbon composite material using a carbon source gas under a protective atmosphere

[0071] In some embodiments of the present invention, a carbon source gas and a protective gas may be introduced into the silicon-carbon composite material in a fluidized state to deposit a carbon coating layer on the surface of the silicon-carbon composite material. This is conducive to further achieving uniform deposition of carbon on the surface of the silicon-carbon composite material. For example, refer to Figure 4 It is understood that the process of depositing the carbon coating on the surface of the silicon-carbon composite material can also be carried out in the collection area.

[0072] In some embodiments of the present invention, when a carbon coating layer is deposited on the surface of a silicon-carbon composite material, the deposition temperature may be 500°C to 700°C, and the time may be 2h to 10h. For example, the deposition temperature may be 500°C, 550°C, 600°C, 650°C, 700°C, and the time may be 2h, 4h, 6h, 8h, 10h, 12h, etc. Controlling the above deposition temperature is beneficial to avoiding the problem of excessively high temperature causing carbon crystallization or excessively large grain size, and is also beneficial to avoiding the problem of low carbon source cracking efficiency due to excessively low temperature. Controlling the above deposition time is beneficial to controlling the thickness of the carbon coating layer, and obtaining a carbon coating layer with a suitable thickness.

[0073] In some embodiments of the present invention, when a carbon coating layer is deposited on the surface of a silicon-carbon composite material, the volume ratio of the carbon source gas to the protective gas may be (5L-10L): (1L-3L), for example, 5L / 3L, 7L / 2L, 5L / 1L, 10L / 3L, 10L / 1L, etc. For example, the carbon source gas flow rate may be 1-3L / min, and the protective gas flow rate may be 5-10L / min. Meeting the above conditions is conducive to further controlling the carbon deposition rate.

[0074] In some embodiments of the present invention, the carbon source gas may include at least one of methanol, acetone, methane, ethane, propane, and acetylene. The protective gas may include but is not limited to argon and / or nitrogen.

[0075] The third aspect of the present invention provides a negative electrode plate. According to an embodiment of the present invention, the negative electrode plate includes: the above-mentioned silicon-carbon composite material; and / or, a silicon-carbon composite material prepared by the above-mentioned method for preparing a silicon-carbon composite material. The features and methods described for the above-mentioned silicon-carbon composite material and the preparation of the silicon-carbon composite material are also applicable to the negative electrode plate, which will not be repeated here. In general, the negative electrode plate has good volume stability during use, which is conducive to the battery having good cycle performance, high energy density and improved first coulomb efficiency.

[0076] A fourth aspect of the present invention provides a battery. According to an embodiment of the present invention, the battery includes: the above-mentioned negative electrode plate. The battery can have good cycle performance, high energy density and improved first coulomb efficiency. Exemplarily, the battery can be a lithium ion battery or a sodium ion battery.

[0077] The fifth aspect of the present invention proposes an electrical device. According to an embodiment of the present invention, the electrical device includes: the above-mentioned battery. The battery life of the electrical device and the battery life are relatively long. It should be noted that the specific type of the electrical device is not particularly limited, and those skilled in the art can flexibly choose according to actual needs. For example, the electrical device may include but is not limited to electronic products, vehicles, household appliances, etc., wherein electronic products include but are not limited to mobile phones, computers, game consoles, etc., and vehicles include but are not limited to pure electric vehicles, hybrid electric vehicles, etc.

[0078] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0079] Example 1

[0080] refer to Figure 4 In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 100g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <10Pa. The material in the collection area is radially rotated to make it in a fluidized state, and the temperature of the collection area is set to 400℃, the rotation speed is 10r / min, and the temperature of the gasification area is 1400℃. After heating to the target temperature, the reaction is kept warm for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0081] Example 2

[0082] refer to Figure 4In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 120g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <50Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, and the gasification area temperature is 1200℃. After heating to the target temperature, the reaction is kept warm for 12 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 400nm; the volume particle size Dv50 of the activated carbon powder is 3μm, and the specific surface area is 1500m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0083] Example 3

[0084] refer to Figure 4 In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 150g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <30Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1600℃, and the temperature is heated to the target temperature and kept warm for 4 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 600nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1800m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0085] Example 4

[0086] refer to Figure 4In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 120g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <10Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, and the gasification area temperature is 1800℃. After heating to the target temperature, the reaction is kept warm for 2h to obtain a silicon-carbon composite material. Among them, the silicon powder is polycrystalline silicon with a Dv50 particle size of 600nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0087] Example 5

[0088] refer to Figure 4 In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 120g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <10Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept warm for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 3μm, and the specific surface area is 1500m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 5 hours, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0089] Example 6

[0090] refer to Figure 4In the device shown, 50g of activated carbon powder is placed in the collection area of ​​the reactor, 60g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <20Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, and the gasification area temperature is 1400℃. After heating to the target temperature, the reaction is kept warm for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 10μm, and the specific surface area is 1500m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 5%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 1h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0091] Example 7

[0092] refer to Figure 4 In the device shown, 200g of activated carbon powder is placed in the collection area of ​​the reactor, 300g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <5Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept warm for 12 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon with a Dv50 particle size of 400nm; the volume particle size Dv50 of the activated carbon powder is 5μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 20%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 4L / min. After the reaction for 5 hours, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0093] Example 8

[0094] refer to Figure 4In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 150g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <10Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon with a Dv50 particle size of 400nm; the volume particle size Dv50 of the activated carbon powder is 5μm, and the specific surface area is 1800m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 5 hours, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0095] Comparative Example 1

[0096] refer to Figure 4 In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 100g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <1000Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept warm for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0097] Comparative Example 2

[0098] refer to Figure 4In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 200g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <10Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0099] Comparative Example 3

[0100] refer to Figure 4 In the device shown, 100g of activated carbon powder is placed in the collection area of ​​the reactor, 200g of silicon powder is placed in the gasification area, and then the reactor is evacuated to a vacuum degree of <1000Pa. The material in the collection area is radially rotated to make it in a fluidized state, the collection area temperature is set to 400℃, the rotation speed is 10r / min, the gasification area temperature is 1400℃, and the temperature is heated to the target temperature and kept warm for 5 hours to obtain a silicon-carbon composite material. Among them, the silicon powder is metallic silicon powder with a Dv50 particle size of 200nm; the volume particle size Dv50 of the activated carbon powder is 6μm, and the specific surface area is 1600m 2 / g, the volume filling rate of activated carbon powder in the collection zone is 10%. After the silicon deposition is completed, the gasification zone is cooled, and the target temperature of the collection zone is set to 650°C. When the temperature of the gasification zone drops below 400°C and the temperature of the collection zone reaches 650°C, acetylene-argon mixed gas is introduced into the system, the volume percentage of acetylene is 30%, and the mixed gas flow rate is 2L / min. After the reaction for 3h, the acetylene-argon mixed gas is turned off, the electric heating is turned off, and finally the system is cooled to room temperature before discharging to obtain a silicon-carbon composite material with a carbon coating layer.

[0101] (1) The silicon-carbon composite materials prepared in each embodiment and comparative example were tested:

[0102] (1-1) After the silicon-carbon composite material is sliced, the average particle size of the silicon-carbon composite nano-silicon particles prepared in each embodiment and comparative example is characterized by using HRTEM electron microscope;

[0103] (1-2) The oxygen content and carbon-silicon mass ratio of the silicon-carbon composite materials prepared in each embodiment and comparative example were tested by inert gas fusion infrared method in combination with a carbon-sulfur analyzer;

[0104] (1-3) Using a specific surface area tester to test the specific surface area of ​​the silicon-carbon composite material prepared in each embodiment and comparative example;

[0105] (1-4) The Dv50 particle size of the silicon-carbon composite material prepared in each embodiment and comparative example was measured using a laser diffraction particle size analyzer.

[0106] (1-5) The true density of the silicon-carbon composite material prepared in each embodiment and comparative example was tested using a true density meter in accordance with the national standard GB / T 24533.

[0107] (2) The electrochemical properties of the silicon-carbon composite materials prepared in each embodiment and comparative example were tested:

[0108] Preparation of negative electrode sheet: using silicon-carbon composite material as negative electrode active material, mixing negative electrode active material, sodium carboxymethyl cellulose (CMC), conductive carbon black (SP) and styrene-butadiene rubber (SBR) in a mass ratio of 94.5:1.5:1.5:2.5 to prepare negative electrode slurry, coating the negative electrode slurry on both sides of the copper foil current collector, vacuum drying to obtain negative electrode sheet;

[0109] Preparation of electrolyte: Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1, and then lithium salt LiPF6 was added to obtain an electrolyte with a lithium salt concentration of 1 mol / L;

[0110] The negative electrode plate is assembled with the lithium plate, electrolyte, and Celgard2400 separator, and the outer shell is assembled with button batteries using conventional production processes.

[0111] The button cell was used as an experimental example to perform charge and discharge cycles at 25°C at a rate of 0.1C, and the initial charge specific capacity and discharge specific capacity were recorded, and the first coulombic efficiency was calculated. The initial discharge specific capacity was used as the initial capacity, and the above cycle operation was repeated, and the discharge specific capacity after 50 cycles was recorded, and the discharge capacity retention rate was calculated.

[0112] Table 1 Differences and test results of Examples 1 to 8 and Comparative Example 1

[0113]

[0114]

[0115] Results and Conclusions:

[0116] It can be seen from the above embodiments and comparative examples that the vacuum degree of the reactor will affect the oxygen content of the finally prepared silicon-carbon composite material, and as the oxygen content of the silicon-carbon composite material increases, the first efficiency and cycle capacity retention rate of the battery will also decrease accordingly. For example, compared with Example 1, the first efficiency in Comparative Example 1 is reduced to 86.3%, and the cycle retention rate becomes 86%; Figure 5 As shown, the area with bright contrast is the area with high silicon content. When the amount of silicon source added is too much, the silicon-carbon ratio is large, and the porous carbon surface is prone to serious surface silicon coating problems. The size of silicon particles will increase rapidly, resulting in poor cycle stability. For example, compared with Example 1, the 50-cycle capacity retention rate in Comparative Example 2 is 83%. Therefore, it is further explained that the present invention adopts a bottom-up physical vapor deposition method to prepare a nano-silicon-carbon composite material, which can not only make silicon uniformly deposited inside the porous carbon material, but also obtain nano-silicon particles with a particle size of 2nm to 10nm, and at the same time improve the Si-C bonding strength; further, the silicon powder is gasified under vacuum conditions, and the oxygen content in the final silicon-carbon composite material can be controlled below 0.5wt%, so as to obtain a silicon-carbon composite material with both high initial efficiency and cycle stability.

[0117] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0118] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that: include: A porous carbon material and nano-silicon particles, at least a portion of the nano-silicon particles are distributed inside the porous carbon material, wherein: The average particle size of the nano silicon particles is 2nm to 10nm; Based on the mass of the silicon-carbon composite material, the oxygen content in the silicon-carbon composite material is ≤0.5wt%.

2. The silicon-carbon composite material according to claim 1, characterized in that: The mass ratio of the nano silicon particles to the porous carbon material is (0.90-1.25):

1.

3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: The silicon-carbon composite material meets at least one of the following three conditions: the volume particle size Dv50 is 3 μm to 10 μm, the specific surface area is ≤10 m 2 / g, true density is 1.8g / cm 3 ~2.0g / cm 3 .

4. The silicon-carbon composite material according to claim 3, characterized in that: The specific surface area of ​​the porous carbon material is ≥1500m 2 / g; and / or, The porous carbon material includes at least one of activated carbon, natural graphite, artificial graphite and carbon nanotubes.

5. The silicon-carbon composite material according to claim 1 or 4, characterized in that: At least a portion of the outer surface of the silicon-carbon composite material is also provided with a carbon coating layer.

6. The silicon-carbon composite material according to claim 5, characterized in that: The thickness of the carbon coating layer is 1 nm to 100 nm; and / or the mass percentage of the carbon coating layer in the silicon-carbon composite material is 1 wt % to 6 wt %.

7. A method for preparing the silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: include: Gasifying silicon powder under vacuum conditions to obtain a gaseous silicon source; The porous carbon material is mixed with the gaseous silicon source in a fluidized state so that the gaseous silicon source is deposited on the surface of the porous carbon, thereby obtaining a silicon-carbon composite material including the porous carbon material and nano-silicon particles, wherein at least a portion of the nano-silicon particles are distributed inside the porous carbon material.

8. The method according to claim 7, characterized in that At least one of the following conditions is met: The volume particle size Dv50 of the silicon powder is 200nm to 600nm; The silicon powder includes metallic silicon and / or polycrystalline silicon; The vacuum degree of the vacuum condition is 5Pa to 50Pa; The temperature of the gasification treatment is 1200°C to 1800°C, and the time is 2h to 12h; The volume particle size Dv50 of the porous carbon material is 3 μm to 6 μm; The temperature of the mixing treatment is 400°C to 600°C; The mixing process is carried out under vacuum conditions or a protective atmosphere; The device for implementing the method comprises a gasification zone and a collection zone, wherein the gasification zone and the collection zone are connectable, the gasification treatment is performed in the gasification zone, the mixing treatment is performed in the collection zone, and the collection zone is rotatable relative to the gasification zone.

9. The method according to claim 7 or 8, characterized in that: Also includes: A carbon coating layer is deposited on the surface of the silicon-carbon composite material using a carbon source gas under a protective atmosphere.

10. The method according to claim 8, characterized in that Passing a carbon source gas and a protective gas into the silicon-carbon composite material in a fluidized state to deposit a carbon coating layer on the surface of the silicon-carbon composite material; and / or, The volume filling rate of the porous carbon material in the collection area is 1% to 10%.

11. The method according to claim 10, characterized in that At least one of the following conditions is met: The deposition temperature is 500°C to 700°C and the deposition time is 2h to 10h; The volume ratio of the carbon source gas to the protective gas is (5L-10L):(1L-3L); The carbon source gas includes at least one of methanol, acetone, methane, ethane, propane, and acetylene; The protective gas includes argon and / or nitrogen.

12. A negative electrode plate, characterized in that: The invention comprises the silicon-carbon composite material according to any one of claims 1 to 6, and / or the silicon-carbon composite material prepared by the method according to any one of claims 7 to 11.

13. A battery, characterized in that: Including the negative electrode sheet as described in claim 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.